Fundamentals and applications of microfluidics - Nguyen, Nam-Trung, 1970- (Microelectromechanical systems series., 2002)
Annotation This introduction to the emerging field of microfluidics explains how to take advantage of the performance benefits of microfluidics and serves as a reference for technology and applications in this area. It offers practical guidance on how to model, design, and fabricate microfluidic devices, and discusses a range of microfluidic applications, including fluid control devices, gas and fluid measurement devices, medical testing equipment, and implantable drug pumps. Calculations, data tables, and rules of thumb are provided to help practitioners make design decisions and determine device characteristics. Nguyen is an assistant professor at the School of Mechanical and Production Engineering at Nanyang Technological University, Singapore. Wereley is an assistant professor of mechanical engineering at Purdue University. Annotation copyrighted by Book News, Inc., Portland, OR.